The Effectiveness of Instructional Program based on Constructivism Theory on Acquiring Geographical Concepts among the Ninth Grade Students in Jordan - Al-Najadat, Muhammad Hussain Faris (Journal of Educational and Psychological Sciences, 2020)
The study aimed to examine The Effectiveness of Instructional Program based on Constructivism Theory on Acquiring Geographical Concepts among the Ninth Grade Students in Jordan. To achieve the goals of the study، a test was designed to measure the acquisition of geographical concepts، and the researcher adopted the semi-experimental approach، as the experimental group consisting of (30) students were taught according to the educational program based on structural theory، and the control group consisting of (30) students were studied in the usual way. Apply the test to the two groups before and after the experiment. The results of analysis ANCOVA showed that there were statistically significant differences at the α05.0 level between the two groups due to the use of constructivism theory learning program. The students who received instruction based on the constructivism theory Achieved higher in acquiring geographical concepts، The study recommended the employment of the proposed educational program in the teaching of Geography and conducting other similar studies in different educational stages and using new variables.